Effect of the transcutaneous electrical stimulation system on esophageal-acid exposure in patients non-responsive to once-daily proton-pump inhibitor: proof-of-concept study. (11th February 2021) - Dickman, Ram; Levy, Sigal; Perets, Tsachi Tsadok; Hazani-Pauker, Maor; Boltin, Doron; Schmilovitz-Weiss, Hemda; Nidal, Issa; Siterman, Matan; Carter, Dan; Fass, Ronnie; Gingold-Belfer, Rachel
Abstract: Background: Gastroesophageal reflux disease (GERD) is a common disorder. Overall, ≤35% of GERD patients fail the standard dose of proton-pump-inhibitor (PPI) treatment. Due to the high prevalence and low satisfaction rate with treatment failure, there is an unmet need for new treatment. Our aim was to evaluate whether the use of the transcutaneous electrical stimulation system (TESS) can reduce esophageal-acid exposure in GERD patients unresponsive to standard-dose PPI. Methods: We enrolled 10 patients suffering from heartburn and regurgitation with an abnormal esophageal-acid exposure (off PPIs) who failed standard-dose PPI. After the placement of a wireless esophageal pH capsule, all patients were treated with TESS. The primary end point was the reduction in the baseline (pretreatment) 24-hour percent total time pH <4 and/or DeMeester score by 50%. Results: Seven GERD patients (five females and two males, aged 49.3 ± 10.1 years) completed the study. At baseline, the mean percent total time pH <4 was 12.0 ± 4.9. Following TESS, the mean percent total time pH <4 dropped to 5.5 ± 3.4, 4.5 ± 2.6, 3.7 ± 2.9, and 4.4 ± 2.5 on Days 1, 2, 3, and 4, respectively. At baseline, the mean DeMeester score was 39.0 ± 18.5. After TESS, the mean DeMeester score dropped to 15.8 ± 9.2, 13.2 ± 6.8, 11.2 ± 9.4, and 12.0 ± 6.8 on Days 1, 2, 3, and 4, respectively. Conclusion: TESS is a safe and potentially effective modality in reducing esophageal-acid exposure in GERD patients unresponsive to standard-dose PPI. A larger and prospective controlled study is needed to verify these preliminary results.